2013
DOI: 10.1016/j.cub.2013.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of the Human Circadian Clock to the Natural Light-Dark Cycle

Abstract: Summary The electric light is one of the most important human inventions. Sleep and other daily rhythms in physiology and behavior however, evolved in the natural light-dark cycle[1] and electrical lighting is thought to have disrupted these rhythms. Yet how much the age of electrical lighting has altered the human circadian clock is unknown. Here we show that electrical lighting and the constructed environment is associated with reduced exposure to sunlight during the day, increased light exposure after sunse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
520
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(584 citation statements)
references
References 40 publications
35
520
4
5
Order By: Relevance
“…Significantly, we did not find that light intensity was associated with chronotype. Initially, these findings appear to contradict earlier studies where increased light exposure is associated with an earlier chronotype in the general population (Roenneberg and Merrow 2007; Wright et al 2013; Roenneberg et al 2015; Stothard et al 2017). However, our findings are derived exclusively from a university student population aged between 17 and 26 years.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Significantly, we did not find that light intensity was associated with chronotype. Initially, these findings appear to contradict earlier studies where increased light exposure is associated with an earlier chronotype in the general population (Roenneberg and Merrow 2007; Wright et al 2013; Roenneberg et al 2015; Stothard et al 2017). However, our findings are derived exclusively from a university student population aged between 17 and 26 years.…”
Section: Discussionmentioning
confidence: 55%
“…A recent study compared the same individuals living under their normal urban routines (including artificial light at night) with a period under natural light exposure (camping without artificial light). The findings demonstrated that increased exposure to natural light advanced the circadian phase of all individuals (Wright et al 2013; Stothard et al 2017). Increasing photic zeitgeber strength by spending more time outside has also been correlated with self-reported chronotype: the more time spent outside, the earlier the chronotype (Roenneberg and Merrow 2007; Roenneberg et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The circadian time-keeping system in humans modulates energy metabolism so that wakefulness, activity, and food intake are promoted during the solar day and sleep, inactivity, and fasting occur during the solar night (2). With the widespread use of electrical lighting, however, work and social activities are capable of being extended further into the night (6,7). Being awake during the biological night leads to disturbed physiology and behavior, because it creates a state of desynchrony between the circadian clock and wakefulness-sleep cycle known as circadian misalignment.…”
mentioning
confidence: 99%
“…Although the people were only retiring to their sleeping bags an hour or so earlier than usual, their melatonin levels started to rise much earlier, around sunset. And rather than lingering in the morning, melatonin levels fell before people woke up (8). "Humans are like other species," says Wright.…”
Section: Outdoor Typementioning
confidence: 99%